2005
DOI: 10.1177/016264340602100101
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cognitive Organizers and Technology-Based Practices on Student Success in Secondary Social Studies Classrooms

Abstract: This study investigated the impact of cognitive organizers, with the integration of technology, Inspiration 6 software, compared to a traditional textbook instruction format on content-area learning in high school inclusive social studies classes. Twenty-nine tenth-grade students in general education and 20 students with mild disabilities were randomly assigned to receive instruction using a cognitive organizer or traditional textbook instruction format. A pretest/posttest treatment control group design was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 21 publications
0
57
0
Order By: Relevance
“…Studies have shown that technology lends itself very well to the social studies curriculum, particularly regarding students with disabilities (Coombs, 2005;Boon et al, 2006). Also, Internet access can democratize the availability of primary sources and allow visits to virtual museums or other educational opportunities that otherwise would remain unexplored (Doolittle & Hicks, 2003;Bolick, 2006).…”
Section: Educational Implications Of the Digital Dividementioning
confidence: 99%
“…Studies have shown that technology lends itself very well to the social studies curriculum, particularly regarding students with disabilities (Coombs, 2005;Boon et al, 2006). Also, Internet access can democratize the availability of primary sources and allow visits to virtual museums or other educational opportunities that otherwise would remain unexplored (Doolittle & Hicks, 2003;Bolick, 2006).…”
Section: Educational Implications Of the Digital Dividementioning
confidence: 99%
“…Several technology based and non-technology based instructional strategies have been used to increase and sustain the interest of students with and without SLD in history classrooms. These strategies include but are not limited to alternative textbooks (Paxton, 2002), graphic organizers (Bulgren, Deshler, & Lenz, 2007), computerized study guides (Boon, Burke, Fore, & Spencer, 2006;Higgins, Boone, & Lovitt, 1996), multimedia-enhanced projects (Ferretti & Okolo, 1997), the use of mnemonic devices (Mastropieri, Scruggs, & Whedon, 1997), and active student responding (Jerome & Barbetta, 2005). For the remainder of this chapter, social studies instructional strategies involving technology will be the primary focus.…”
Section: Instructional Strategies For Historymentioning
confidence: 99%
“…Furthermore, Nokes (2008) proposed that secondary social studies classrooms should integrate modern learning theories and the new age of information with history instruction. Instructional strategies involving technology have been particularly helpful in facilitating learning gains in history for students with and without SLD (Berson, 1996;Boon, Burke, Fore, & Spencer, 2006).…”
Section: Instructional Strategies For Historymentioning
confidence: 99%
See 2 more Smart Citations